Provision of public goods: Unconditional and conditional donations from outsiders - Esther Blanco; Tobias Haller; James M. Walker (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
The provision of public goods often benefits a larger group than those who actively provide the public good. In an experimental setting, this paper addresses institutional arrangements between subjects who can provide a public good (insiders) and subjects who benefit from the public good but cannot provide it (outsiders). We compare a setting of passive outsiders to situations where outsiders can either make unconditional transfers (donations) or conditional transfers (contracts) to the insiders. The primary behavioral question is to what extent outsiders will respond to the opportunity to subsidize the contributions of insiders and will insiders use such subsidies to increase contributions or simply substitute them for their own contributions. The results suggest the latter. In fact, once conditional or unconditional transfers are allowed, insiders decrease contributions to the public good relative to the baseline condition without transfers.
Keywords: D70; H41; C92; 330; Public goods; Institution; Externality; Laboratory Experiment